The improvement of right ventricular function after adenotonsillectomy in children with obstructive sleep apnea - Dong Yeop Kim; Kyung Ok Ko; Jae Woo Lim; Jung Min Yoon; Young Hwa Song; Eun Jeong Cheon (Korean Pediatric Society, 2018)
Purpose Adenotonsillar hypertrophy (ATH) that causes upper airway obstruction might lead to chronic hypoxemic pulmonary vasoconstriction and right ventricular (RV) dysfunction. We aimed to evaluate whether adenotonsillectomy (T&A) in children suffering from obstructive sleep apnea (OSA) due to severe ATH could improve RV function. Methods Thirty-seven children (boy:girl=21:16; mean age, 9.52±2.20 years), who underwent T&A forsleep apnea due to ATH, were included. We analyzedthe mean pulmonary artery pressure (mPAP), the presence and the maximal velocity of tricuspid regurgitation (TR), the tricuspid annular plane systolic excursion (TAPSE), and the right ventricular myocardial performance index (RVMPI) with tissue Doppler echocardiography (TDE) by transthoracic echocardiography pre- and post-T&A. The follow-up period was 1.78±0.27 years. Results Only the RVMPI using TDE improved after T&A (42.18±2.03 vs. 40±1.86, P=0.001). The absolute value of TAPSE increased (21.45±0.90 mm vs. 22.30±1.10 mm, P=0.001) but there was no change in the z score of TAPSE pre- and post-T&A (1.19±0.34 vs. 1.24±0.30, P=0.194). The mPAP was within normal range in children with ATH, and there was no significant difference between pre- and post-T&A (19.6±3.40 vs. 18.7±2.68, P=0.052). There was no difference in the presence and the maximal velocity of TR (P=0.058). Conclusion RVMPI using TDE could be an early parameter of RV function in children with OSA due to ATH.